Blocking TRAIL-DR5 signaling pathway with soluble death receptor 5 fusion protein mitigates radiation-induced injury - Zhao, Danyang; Yang, Lei; Han, Peng; Zhang, Haihui; Wang, Fanjun; Meng, Zhiyun; Gan, Hui; Wu, Zhuona; Sun, Wenzhong; Chen, Chuan; Dou, Guifang; Gu, Ruolan (Frontiers in Pharmacology, 2023)
The increasing application of nuclear technology, the high fatality of acute radiation syndrome (ARS) and its complex mechanism make ARS a global difficulty that requires urgent attention. Here we reported that the death receptor 5 (DR5), as well as its ligand tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), were both significantly upregulated after irradiation in mice with 6 Gy γ-ray single radiation. And by intravenously administrated with soluble DR5 fusion protein (sDR5-Fc), the competitive antagonist of DR5, the excessive apoptosis in the radiation-sensitive tissues such as spleen and thymus were significantly inhibited and the radiation-induced damage of spleen and thymus were mitigated, while the expression of apoptosis-inhibiting proteins such as Bcl-2 was also significantly upregulated. The biochemical indicators such as serum ALP, AST, ALT, TBIL, K, and Cl levels that affected by radiation, were improved by sDR5-Fc administration. sDR5-Fc can also regulate the number of immune cells and reduce blood cell death. For in vitro studies, it had been found that sDR5-Fc effectively inhibited apoptosis of human small intestinal mucosal epithelial cells and IEC-6 cells using flow cytometry. Finally, survival studies showed that mice administrated with sDR5-Fc after 9 Gy γ-ray single whole body radiation effectively increased the 30-day survival and was in a significant dose-dependent manner. Overall, the findings revealed that DR5/TRAIL-mediated apoptosis pathway had played important roles in the injury of ARS mice, and DR5 probably be a potential target for ARS therapeutics. And the DR5 apoptosis antagonist, sDR5 fusion protein, probably is a promising anti-ARS drug candidate which deserves further investigation.